Breakwater Effectiveness to Reduce Ocean Waves In The Karangantu Fisheries Port, Serang City, Banten Province, Indonesia - Seruni Ajeng Amiati; Waluyo Waluyo; Amdani Amdani (Grouper: Fisheries Scientific Journal, 2020)
The ease of mooring anchorage in a port is influenced by the level of the calm of the waters. The dynamics of wave movement found in coastal areas, especially in the anchorage pool area, are caused by several factors including the influence of wind, currents, tides and the action of ocean waves. For this reason, one of the most important coastal protective structures is Breakwater which is expected to reduce and reduce the effects of ocean waves. This research was conducted in November 2019 at the Karangantu Port of Fisheries (PPN) in Karangantu, Serang Regency, Banten Province. The purpose of this study was to determine the level of effectiveness of breakwater as a shock wave for mooring boat anchors at PPN Karangantu, Banten. This research method uses quantitative analysis based on primary wave height data which is connected with some secondary data, to produce the value of the wave transmission coefficient and the effectiveness percentage of sea wave attenuation. Based on the results of the study showed that the average height of the incident wave was 224.60 cm and the average height of the transmission wave was 169.66 cm. The results of the analysis showed that the average value of the transmission coefficient was 1.32 and the level of effectiveness of the breakwater in absorbing the waves was 24.42%. Based on the value of the effectiveness of the breakwater it can be said that the existing breakwater at the Port of Karangantu, Serang Regency is quite effective in reducing the incident wave action..